DONOR DARAH DENGAN HIPERLIPIDEMIA BERDAMPAK TERHADAP KUALITAS DARAH YANG DISUMBANGKAN: SYSTEMATIC REVIEW - Anzhari, Della Hashfi; Ritchie, Ni Ken; Lubis, Anna Mira (Poltekkes Kemenkes Bandung, 2024)
Hyperlipidemia is currently suffered by many people, including those individuals who regularly donate blood. Hyperlipidemia occurs due to an unhealthy lifestyle. It was found that there was a decrease in the quality of donor blood, including a change in plasma color to a milky white, cloudy appearance known as lipemia, as well as a decrease in the function of platelet and erythrocyte components. The aim of this study was to determine the impact of hyperlipidemia in blood donors on the blood produced. This systematic literature review follows PRISMA guidelines, with article collection carried out using basic data from Science Direct, PubMed, Google Scholar, Research Gate and Sage Journal. The articles used were limited to publication years between 2014 and 2024. In this research, 7 articles were found that were suitable and selected. The results of this study show that there are several factors that cause an individual to experience hyperlipidemia, one of the factors that has a big influence is diet. In this study, it was discovered that donors with hyperlipidemia were more likely to produce blood products that had high levels of fat, in which case the plasma blood component became lipemic and level of hemolysis during storage was higher. Apart from that, hyperlipidemia also affects other blood products, namely the platelet component, which can produce platelets that have abnormalities in platelet composition and function. The impact of hyperlipidemia should not be ignored, better donor screening can provide better quality control to reduce the risk of this occurring.